INVESTIGATING THE APPLICATION OF SERVICE MODULARISATION IN AN INDUSTRY: - “A CASE STUDY OF A MOBILE OPERATOR IN SIERRA LEONE (AIRTEL) AND A MONEY TRANSFER SERVICE IN THE UNITED KINGDOM (WESTERN UNION)” - Thompson, Jonathan C. E. O (2017)
Abstract There is an increasing trend in the need for services, and organisations are now moving towards modularisation of their services for efficiency, competitive advantage and to satisfy their customers. Modularisation activities focuses on standardisation, customisation and the reduction of complexity in its system to achieve efficiency, cost minimisation and better service for business growth. The main objective of this study is to examine how theory and practice relates; which involves bringing out concepts of modularity from literatures and examine practical cases in the service industry. Interest in the field of modularity is emerging, in order to discover how the implementation of modularity can add value to research and practical application. Therefore, this dissertation seeks to arrive at strategic decisions that should be considered in the implementation of modularisation and identifying the factors that influences the implementation of modularisation in a money transfer service. To achieve this, two case studies were selected, a Mobile Money Transfer Service System in Sierra Leone and the Western Union Money Transfer Service in the United Kingdom. According to the results the application of modularisation in a service organisation can enhance service efficiency, customers’ satisfaction and contributes greatly in business development by gaining competitive advantage and increase in profit.